Mining Stock Price Index on Macro Economic Indicators - Eso Hernawan; Temmy Setiawan Setiawan; Andy Andy; Peng Wi (eCo-Fin, 2020)
This study aims to examine the effect of the BI Rate, exchange rate and inflation on the stock price index of building mining sector companies listed on the Indonesia Stock Exchange for the period January 2015 to December 2018. The data analysis technique used in this study is the regression model. The test results prove that the BI Rate (X1) has an effect on the IHSP with a statistical t value of -5.697072 > t-table 2.01537 and a probability value of 0.00 < 0.05, then H1 is accepted. The exchange rate (X2) has an effect on the IHSP with a statistical t value of 4.263165 > t-table 2.01537 and a probability value of 0.0001 < 0.05, then H1 is accepted. The exchange rate has a negative effect on the IHSP with a statistical t value of -1.321528 < t-table 2 0.01537 and 01932 probability value > 0.05, then H1 rejects. To determine the effect of jointly used F test where the results of BI Rate, Exchange Rate and Inflation simultaneously affect the IHSP which is indicated by F-count 54.35844 > F-Table l2.21 and the probability value of F-statistics is F-statistic 0.0000 < 0.05 , then H1 is accepted, with a simultaneous effect of 58.33%. while the remaining 41.67% is explained by other variables not examined in this study